Relationship Between ABO Blood Groups and Mental Disorders - Ajdacic-Gross V; Buadze A; Wagner EYN; Müller M; Seifritz E; Ranjbar S; Glaus J; Castelao E; Strippoli MPF; Vandeleur CL; Preisig M; von Känel R (Journal of Blood Medicine)
Vladeta Ajdacic-Gross,1 Ana Buadze,1 En-Young N Wagner,2 Mario Müller,1 Erich Seifritz,1 Setareh Ranjbar,3 Jennifer Glaus,4 Enrique Castelao,3 Marie-Pierre F Strippoli,3 Caroline L Vandeleur,3 Martin Preisig,3 Roland von Känel2 1Department of Adult Psychiatry and Psychotherapy, Psychiatric University Clinic Zurich and University of Zurich, Zurich, Switzerland; 2Department of Consultation-Liaison Psychiatry and Psychosomatic Medicine, University Hospital Zurich and University of Zurich, Zurich, Switzerland; 3Department of Psychiatry, Psychiatric Epidemiology and Psychopathology Research Center, Lausanne University Hospital and University of Lausanne, Prilly, Switzerland; 4Department of Psychiatry, Service of Child and Adolescent Psychiatry, Lausanne University Hospital and University of Lausanne, Lausanne, SwitzerlandCorrespondence: Vladeta Ajdacic-Gross, Department of Adult Psychiatry and Psychotherapy, Psychiatric University Clinic Zurich and University of Zurich, PO Box 2019, CH-8032, Zürich, Switzerland, Tel +41 79 921 36 80, Email vladeta.ajdacic-gross@uzh.chAbstract: Previous research has unveiled an intriguing positive association between the AB blood group and mental disorders in general. In this study, we compared ABO blood groups with five major groups of mental disorders to attain a higher level of specificity. The analyses were conducted using data from the CoLaus|PsyCoLaus study (N=5111). They revealed that the AB blood group exhibited a positive association with both neurodevelopmental disorders (RR 2.29, CI 1.38– 3.82) and substance use disorders (RR 2.25, CI 1.38– 3.65) after adjusting for sex and childhood adversities. These associations could be replicated with respect to the familial aggregation of neurodevelopmental and substance use disorders. Large databases are needed to achieve more detailed results related to specific disorders.Plain Language Summary: Prior research has shown an interesting link between the AB blood group and mental disorders. In our study, we used data from a large Swiss population-based epidemiological cohort study to learn more about this connection. We examined the relationship between ABO blood groups and five major groups of mental disorders: neurodevelopmental, early onset anxiety, later onset anxiety, mood, and substance use disorders. Our analyses revealed associations between the AB blood group and neurodevelopmental and substance use disorders. The findings point to an unknown immunological mechanism that may play a role in the development of neurodevelopmental and substance use disorders.Keywords: ABO blood groups, neurodevelopmental disorders, substance use disorders, familial aggregation